(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
The aim of the research is to investigate the effect of Glingham’s strategy on teaching reading skill for first graders of basic education in Arabic language in comparison with the used methods. The current research used the experimental method with an experimental design (equal groups design), as this design includes two equal groups in a number of variables, the first was taken as an experimental group taught according to the educational program according to the Gillingham strategy, and the other is a control group and studied by the methods followed. The two groups were pre-tested on the (reading skills test), then the experimental group was subjected to the independent variable (the educational program according to the Gillingham strategy) and was excluded from the control group that studied the methods followed, then the two groups were post-tested on the (reading skills test), to measure the effect of the Gillingham strategy on developing skills Reading for first graders of basic education in Arabic language. The research showed a set of results, the most important of which were: There is a statistically significant difference between the mean scores of the experimental group members in the direct pre and post applications of reading skills test in favor of the post application. This indicates the effect of Glingham’s strategy on developing reading skills for first graders of basic education in Arabic language.